Dielectric properties and relaxor behavior of PIN based system - Supattra Wongsaenmai (2018)
Several compositions in the two PIN based systems (1-x)Pb(In0.5Nb0.5)O3-(x) PbTiO3 and (0.8-x)Pb(In0.5Nb0.5)O3-(x)PbTiO3-0.2BaTiO3 (x = 0.0, 0.1, 0.2 and 0.3) were synthesized via the wolframite method. Dielectric properties were measured in the frequency range between 100 Hz and 100 kHz and were analyzed for understanding relaxor behavior in the system. The temperature dependence of the dielectric properties was analyzed by studying the deviation from the Curie-Weiss law while the frequency dependence of the dielectric properties was analyzed by the Vogel-Fulcher relation. The results showed that the addition of BT increased the dielectric constant and decreased the shift of the maximum dielectric constant temperature (Tm) of (1-x)PIN-(x)PT compositions. Finally, the analysis also confirmed that, when added to PIN, PT decreased and BT increased the relaxor behavior of the PIN-based ceramics. © Taylor & Francis Group, LLC.